2017
DOI: 10.1097/ftd.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Sampling for Tacrolimus and Mycophenolic Acid in Children: Analytical and Clinical Validation

Abstract: A DBS assay was developed for tacrolimus and MPA. Tacrolimus venous concentrations could be adequately predicted from DBS. DBS analysis of MPA seemed to be a semiquantitative measurement at the most when compared with conventional plasma analysis, considering the high variability between observed and predicted concentrations. Next, home-based DBS sampling of tacrolimus for the purpose of therapeutic drug monitoring will be implemented into routine clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…For mycophenolic acid, the observed geometric mean DBS to plasma concentration ratio of 0.66 was in line with those described by Martial et al . and Arpini et al . , who reported ratios of 0.77 ( n = 38) and 0.61 ( n = 77), respectively.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…For mycophenolic acid, the observed geometric mean DBS to plasma concentration ratio of 0.66 was in line with those described by Martial et al . and Arpini et al . , who reported ratios of 0.77 ( n = 38) and 0.61 ( n = 77), respectively.…”
Section: Discussionmentioning
confidence: 91%
“…With regard to the DBS to WB or plasma conversion factors, a few similar studies could be identified. For tacrolimus, the observed geometric mean DBS to WB concentration ratio of 0.93 was not in line with the conversion factor of 1.31 ( n = 40) reported by Martial et al ., who found higher tacrolimus concentrations in DBS than in WB . Various other studies ( n = 18–172) in adult and paediatric solid organ transplantation have been performed on the subject, and reported a range of geometric mean differences of −0.70 to +0.29 μg l −1 between tacrolimus DBS and WB concentrations .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations